(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To develop and validate the Wound Diary for patients undergoing enterostomal therapy, focusing on chronic skin wounds in the lower limbs. Method: This was a methodological study. The evaluation followed a structured process of content and appearance validation to assess the appropriateness of the objectives, content, style, organization, and images of the material. Validation was conducted by expert judges in the field, who rated the diary based on relevance, clarity, and applicability. Data were analyzed using the Content Validity Index (CVI). Results: Validation indicated that the Wound Diary achieved a CVI higher than 0.75 and a Kappa coefficient above 0.63 across all evaluated criteria, demonstrating a high level of agreement among experts. These results showed the material’s adequacy and relevance for providing patients with pertinent information and encouraging self-care. Conclusion: The Lower Limb Wound Diary was considered valid by the experts, covering all assessed topics. Additionally, the study highlighted the relevance of integrating educational technologies and health education to meet the needs of patients with chronic skin lesions, improving their quality of life and promoting effective collaboration between patients and healthcare professionals.